A solar hybrid system integrating concentrating photovoltaic direct steam generation by chemical heat pump. (15th September 2019) - Wang, Ruilin; Hong, Hui; Sun, Jie; Jin, Hongguang
Highlights: Solar hybrid system integrating photovoltaic and solar thermal power is proposed. Dissipated heat of concentrating photovoltaic is upgraded by chemical heat pump. The heat of chemical heat pump is converted into electricity by steam Rankine cycle. Solar-electric efficiency of hybrid system is more than 20% higher than references. The energy storage function of chemical heat pump enhances the system performance. Abstract: A hybrid solar power generation system integrating a concentrating photovoltaic, direct steam generation solar collector with a chemical heat pump is proposed in this study. In the hybrid system, the chemical heat pump is used to chemically upgrade the dissipated heat of the concentrating photovoltaic. The upgraded heat, together with the heat from the direct steam generation solar collector, is applied to drive the high-parameter steam Rankine cycle for efficient power generation. The performance of the hybrid system was examined first, and it was found that the solar-to-electric efficiency of the hybrid system is more than 20% higher than that of the individual systems of concentrating photovoltaic and direct steam generation solar power generation systems. The influence of chemical heat pump on the performance of the hybrid system is analysed, and the efficiency of the hybrid system reaches the maximum (34.71%) when the exothermic temperature of the chemical heat pump equals 360 °C. The dissipated heat of the concentrating photovoltaic can be chemically stored in the chemical heat pump. This enables the hybrid system to generate electricity continuously. The performance of the hybrid system in a typical day is compared with the concentrating photovoltaic individual system. The result shows that, benefitting from better performance and energy storage, the average electricity output per aperture area of the hybrid system (192.36 Wm −2 ) is approximately 170% higher than that of individual system of concentrating photovoltaic (70.41 Wm −2 ). Integrating the dissipated heat of concentrating photovoltaic into a high efficiency cycle via the chemical heat pump, this work would provide a potential approach for utilizing solar energy efficiently.